Stage, Grade, and Pre-Operative Red Cell Distribution Width (RDW) Associated with Mortality of Colorectal Cancer Patients at Prof. Dr. I.G.N.G Ngoerah Hospital, Bali - Ratmayanti, Made Ayu Laksmi; Sueta, Made Agus Dwianthara; Sudartana, I Ketut (Indonesian Journal of Cancer, 2025)
Background: Colorectal cancer is a world health problem with a high mortality rate and low survival rate. Previous studies have shown that factors such as age, histopathological type, TNM stage, and red cell distribution width (RDW) can influence patient mortality. This study aimed to evaluate the factors associated with the mortality of colorectal cancer patients at Prof. Dr. I.G.N.G Ngoerah Hospital, Bali.Method: This is an analytical observational study with a case-control design in the Department of Digestive Surgery, Prof. Dr. I.G.N.G Ngoerah Hospital, Bali, from April to August 2023. This study included colorectal cancer patients aged 18, within a study period, and with known clinical outcomes. Patients with incomplete medical records and severe comorbidity were excluded from this study. Statistical analysis was carried out with SPSS ver 20.0 for univariate, receiver operating characteristic (ROC) curve, bivariate, and multivariate tests.Results: This study collected 118 samples, divided into 59 dead patients (cases) and 59 living patients (controls). Most of the colorectal cancer patients who died were stage IV patients (62.7%), had higher pre-operative RDW values (15.91 ± 4.14), and 20.3% were poorly differentiated. Multivariate analysis showed that stage IV (p = 0.04), poorly differentiated grade (p = 0.04), and pre-operative RDW 13,575 ( 0.001) were independent factors of mortality in colorectal cancer patients. Conclusion: Stage, grade, and pre-operative RDW affected the mortality of colorectal cancer patients at Prof. Dr. I.G.N.G Ngoerah Hospital, Bali.